Papillary renal neoplasm with reverse polarity and renal clear cell carcinoma: a case report of image–pathology–molecular multidimensional diagnosis and nephron sparing surgery practice - Liu, Yuxuan; Wang, Yanchen; Guan, Lihui; Sun, Shuping; Sun, Huimin; Sun, Yaofei (Frontiers in Oncology, 2026)
Papillary renal neoplasm with reverse polarity (PRNRP) is a new pathological type of renal tumor, and its incidence is low. It is considered to be an indolent renal tumor at present. It is rare for PRNRP to co-occur with other tumors in the same kidney. Like other renal tumors, patients with PRNRP do not have any specific clinical manifestations. During surgery, we resected a solid and a cystic lesion in the left kidney simultaneously, and performed two partial nephrectomy on the ipsilateral kidney at one time, both with good surgical results. The postoperative pathological results were as follows: (1) solid lesions are PRNRP, and (2) cystic lesions are RCCC. Here, we present a case of PRNRP concurrent with RCCC and review the literature.